2008
DOI: 10.1210/en.2008-0949
|View full text |Cite
|
Sign up to set email alerts
|

Metal Transcription Factor-1 Is Involved in Hypoxia-Dependent Regulation of Placenta Growth Factor in Trophoblast-Derived Cells

Abstract: Placenta growth factor (PlGF) is a placental angiogenic factor. Metal-responsive transcription factor (MTF)-1 was reported to take part in the hypoxic induction of PlGF in RAS-transformed mouse fibroblasts. We contrarily showed that PlGF mRNA and protein levels decreased under hypoxia in a choriocarcinoma BeWo cell line derived from trophoblast. In this report, we examined whether hypoxia-dependent regulation of the PlGF gene in these cells also depends on MTF-1. We analyzed the effect of hypoxia on MTF-1 expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…MTF-1 is activated in cultured sheep pulmonary artery endothelial cells following treatment with a NO donor[31]. Interestingly, MTF-1 expression is decreased under hypoxic conditions in trophoblast and has been implicated in the hypoxic regulation of PGF[32]. The potential effects of NO modulation on MTF-1 expression and/or function in trophoblast are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…MTF-1 is activated in cultured sheep pulmonary artery endothelial cells following treatment with a NO donor[31]. Interestingly, MTF-1 expression is decreased under hypoxic conditions in trophoblast and has been implicated in the hypoxic regulation of PGF[32]. The potential effects of NO modulation on MTF-1 expression and/or function in trophoblast are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have shown that PlGF transcriptional activity is mediated in part by glial cell missing-1 (GCM1) transcription factor in trophoblast [27]. Similarly, metal transcription factor-1 (MTF1) has re cently been shown to regulate PlGF expression in trophoblast [42]. Both of these transcription factors are decreased in hypoxic trophoblast in vitro and in preeclamptic trophoblast in vivo [27;42;43].…”
Section: Discussionmentioning
confidence: 99%
“…TGF-b3 also promotes the production of sEng (Mano et al 2011). In addition, VEGF and PlGF are induced under hypoxic conditions (Tissot van Patot et al 2004;Nishimoto et al 2009) and are inhibited by sFlt-1. Interestingly, sEng and sFlt-1 expression are both stimulated under ischemic conditions, thus contributing to the systemic endothelial dysfunction (Gilbert et al 2007(Gilbert et al , 2009).…”
Section: Mechanisms Of Placentation Defects In Preeclampsiamentioning
confidence: 99%